Differences in Pelvic Floor Muscle Strength Before and After Normal Delivery in Patients Who Give Birth in The Working Area of The Padang City Public Health Center - Muhammad Al Fath; Yulia Margaretta Sari; Firdawati Firdawati; Yusrawati Yusrawati; Bobby Indra Utama; Puja Agung Antonius (Andalas Obstetrics And Gynecology Journal, 2026)
Background: Vaginal delivery can cause physiological changes in the pelvic floor muscles and increase the risk of dysfunction such as urinary incontinence or pelvic organ prolapse. However, the extent to which uncomplicated vaginal delivery affects pelvic floor muscle strength is unknown, especially in the Padang City Community Health Center (Puskesmas) area. Objective: To determine differences in pelvic floor muscle strength before and after vaginal delivery in patients who gave birth in the Padang City Community Health Center (Puskesmas) area. Methods: This was a prospective cohort study with 30 primigravida respondents who met the inclusion criteria. Muscle strength was measured using perineometry in the final trimester and 3 months postpartum. Data were analyzed using a paired t-test (α = 5%). Results: The average age of respondents was 28.27 years. Statistical tests showed no significant difference in pelvic floor muscle strength before and after delivery (p = 0.792), indicating that postpartum strength does not affect pre-delivery strength. Conclusion: Uncomplicated vaginal delivery does not significantly affect pelvic floor muscle strength. Decreased strength may be influenced by other factors such as obstetric trauma, birth weight, and exercise during pregnancy. Longer-term follow-up studies are needed for a more comprehensive understanding.